Dissemination of salted fish dryer based on biomass energy for fishermen in Muara Badak Ilir Village, Kutai Kartanegara - Suparno Suparno; Agus Hariyanto; Zainal Arifin (Community Empowerment, 2021)
Tembang and anchovy fish caught by fishermen from Muara Badak Ilir are generally processed into dried salted fish. Currently, the fish drying process is carried out in unsanitary environmental conditions and is highly dependent on the weather. The fish are dried on a rack which is placed in the field and takes 2-3 days. The purpose of this community service is to assist fishermen in solving fish drying problems by designing a mechanical drying device, namely a tray dryer with a capacity of 100 kg. The activities are carried out in four stages, namely: (1) the interview stage; (2) tool design stage; (3) training stage; and (4) evaluation. The service team ensures that the dried salted fish produced meets SNI 8273:2016 standards. The results of the activity evaluation shows that partners are very satisfied with the service activities carried out. The application of a tray dryer based on biomass energy is expected to help increase the productivity of fishermen so that they can increase the welfare of fishermen in the Muara Badak Ilir area.